Mechanical Properties and Crystal Structures of Hydrogenated Titanium Aluminides - Han, Chang-Suk (Asian Journal of Chemistry, 2015)
Structures of the Ti-Al-Zr alloys have been investigated by the X-ray diffractometer. Two ternary intermetallic compounds having the B2 and L21 structures were newly found in the present work. The B2 compound shows some compressive ductility, but the L21 compound shows no ductility at room temperature. Structural changes of the binary and ternary titanium aluminides exposed in a hydrogen atmosphere were investigated. No structural change was detected by hydrogenation of TiAl, but the transformation from the D019 to the fcc structure was observed in Ti3Al. On the contrary, hydrogen induced amorphization was observed in the ternary aluminides with the B2 and L21 structures.